Dokhmenashini and Khurshed Nagirashni mode of disposal of the dead body of a Parsi Zoroastrian : Late Kaikhushro Jamshedji Dubash memorial volume - Dubash, Kaikhushro Jamshedji, 1881-1959 (H. R. Bana, 1970)
Polemic against reformist Parsees; comprises essays, extracts, and previously published letters in support of the traditional method for the disposal of the dead.